2015
DOI: 10.1142/s0192415x15500081
|View full text |Cite
|
Sign up to set email alerts
|

Induction of α-Phellandrene on Autophagy in Human Liver Tumor Cells

Abstract: α-Phellandrene (α-PA) is a cyclic monoterpene. To investigate the induction of autophagy by α-PA and its mechanism, human liver tumor cells (J5) were incubated with α-PA and analyzed for cell viability and the molecular regulation of pre-autophagosome origination and autophagosome formation. According to the results, PI3K-I, mTOR, and Akt protein levels were decreased after α-PA treatment compared to those of the control group (p < 0.05). The phosphorylation of Bcl-2, and PI3K-III, LC3-II and Beclin-1 protein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 39 publications
0
15
0
Order By: Relevance
“…Increasing evidence has been presented that autophagy plays a crucial role in tumor suppression [18]. Findings from a number of reports directed at assessing natural extracts or traditional herbs for use in cancer treatment have revealed that their cytotoxic effects involve the induction and regulation of autophagy [19, 20]. Autophagy can serve as a means to promote cell survival or, contrarily, cell death in tumor cells treated with chemotherapeutic agents [21].…”
Section: Introductionmentioning
confidence: 99%
“…Increasing evidence has been presented that autophagy plays a crucial role in tumor suppression [18]. Findings from a number of reports directed at assessing natural extracts or traditional herbs for use in cancer treatment have revealed that their cytotoxic effects involve the induction and regulation of autophagy [19, 20]. Autophagy can serve as a means to promote cell survival or, contrarily, cell death in tumor cells treated with chemotherapeutic agents [21].…”
Section: Introductionmentioning
confidence: 99%
“…α-phellandrene also alters the expression of cell cycle checkpoint genes such as cyclin G2 and the CDK inhibitor p21, in addition to several apoptosis regulatory factors including caspases [52]. Hsieh LC et al [53] have demonstrated that sub-micromolar concentrations of α-phellandrene promote cell death by autophagy through modulating the expression of mTOR and LC-3II, p53 signaling and NF-KB activation in J5 liver tumor cells. In addition, the toxicity of this compound involves necrosis when tested in liver cancer cell lines [54].…”
Section: Discussionmentioning
confidence: 99%
“…This is particularly obvious with the finding that the general caspase-inhibitor is only able to reverse ∼30% of the oil induced apoptosis in MDA-MB-2 31 compared to ∼60% in MCF-7 cells. The fact that the essential oils of P. spinosa contain compounds that promote cell death by autophagy [53], activation of MAPKs [50], production of ROS [51] and cell cycle arrest [51], proposes that they may also contribute to the cytotoxicity of F-PSEO and L-PSEO.…”
Section: Discussionmentioning
confidence: 99%
“…rigida (0.1%) [21] Z. clinopodioides subsp. bungeana [201] Z. tenuior (0.48%) [94,179] Insecticidal activity against various species of insects [192,193]; larvicidal activity against various mosquito species [205,206] Antinociceptive activity assessed in various chemical-induced nociception models in rodents [207,208] Antidepressant activity in rats [208] Induction of autophagy in human liver tumour cells [209]; induction of necrosis [210]; induction of apoptosis in mice leukaemia WEHI-3 cells in vitro [211]; promotion of the immune response by increasing the level of T-cells, monocytes and macrophages in BALB/c mice in vivo [212] Molecules 2016, 21, 826 14 of 53…”
Section: α-Thujene (34)mentioning
confidence: 99%
“…clinopodioides (2.0%) [184] Inhibition of P-glycoprotein-mediated transport of different substances [213] Suppression of CNS in mice [214,215] Some topical anti-inflammatory activity in carrageenan-induced paw edema in rats [216] Antioxidant activity in various free radical scavenging tests [217,218] Antifungal activity tested against some food spoilage yeasts [219] Larvicidal activity against mosquitoes Aedes aegypti and A. albopictus [206] Antiviral activity against herpes simplex virus type 1 in vitro [220] Review on some effects on cardiovascular system [221] Trypanocidal activity against Trypanosoma evansi [222] Z. tenuior (0.48%) [94,179] α-Phellandrene (35) Z. clinopodioides (0.3%) [184] Insecticidal activity against various species of insects [192,193]; larvicidal activity against various mosquito species [205,206] Antinociceptive activity assessed in various chemical-induced nociception models in rodents [207,208] Antidepressant activity in rats [208] Induction of autophagy in human liver tumour cells [209]; induction of necrosis [210]; induction of apoptosis in mice leukaemia WEHI-3 cells in vitro [211]; promotion of the immune response by increasing the level of T-cells, monocytes and macrophages in BALB/c mice in vivo [212] α-Terpinene (36)…”
Section: α-Thujene (34)mentioning
confidence: 99%